Barbara De Cock, Profiling discourse participants. Forms and functions in Spanish conversation and debates. John Benjamins, Amsterdam-Philadelphia, 2014; 307 pp. (Pragmatics & Beyond New Series, 246). - Vázquez Laslop, María Eugenia (El Colegio de México, 2017)
Se reseñó el libro: Profiling discourse participants. Forms and functions in Spanish conversation and debates.